A survey of manufacturing and handling practices for monoclonal antibodies by pharmacy, nursing and medical personnel. (April 2016) - Alexander, M; King, J; Lingaratnam, S; Byrne, J; MacMillan, K; Mollo, A; Kirsa, S; Green, M
Introduction: There is a paucity of data available to assess the occupational health and safety risk associated with exposure to monoclonal antibodies. Industry standards and published guidelines are conflicting or outdated. Guidelines offer contrary recommendations based on an array of methodological approaches. This survey aimed to describe current practices, beliefs and attitudes relating to the handling of monoclonal antibodies by Australian medical, nursing and pharmacy clinicians. Methods: An electronic survey was distributed between June and September 2013. Respondents were surveyed on three focus areas: institutional guideline availability and content, current practices and attitudes. Demographic data relating to respondent and primary place of practice were also collected. Results: A total of 222 clinicians completed the survey, with representation from all targeted professional groups and from a variety of geographic locations. 92% of respondents reported that their institution prepared or administered monoclonal antibodies, with 87% specifically handling anti-cancer monoclonal antibodies. Monoclonal antibodies were mostly prepared onsite (84–90%) and mostly within pharmacy clean-rooms (75%) and using cytotoxic cabinets (61%). 43% of respondents reported access to institutional monoclonal antibody handling guidelines with risk reduction strategies including training and education (71%), spill and waste management (71%), procedures for transportation (57%) and restricted handling (50%). Nurses had a stronger preference towards pharmacy manufacturing than both doctors and pharmacists for a range of clinical scenarios. 95% of all respondents identified that professional or regulatory body guidelines are an important resource when considering handling practices. Conclusion: Monoclonal antibodies are most commonly handled according to cytotoxic drug standards and often in the absence of formal guidelines.